Boosters in academic discourse: contrastive analysis concerning their use in theses from the fields of social sciences and natural sciences - Álvarez-Gil, Francisco J.; Quintana-Toledo, Elena (Círculo de Lingüística Aplicada a la Comunicación, 2024)
In this paper, a corpus linguistics study is performed to analyse the metadiscursive function as boosters of three adverbials, namely absolutely, highly and strongly, in two subcorpora of doctoral dissertations. These dissertations are written in English and were submitted to Spanish universities between the years 2011–2021. The corpus contains more than ten million words overall, with one subcorpus corresponding to the field of the natural sciences and the other to the social sciences. The goals of the present study are twofold. On the one hand, from a quantitative perspective, we aim to determine the number of cases in which these three adverbials play the role of boosters and compare the results of the two subcorpora. On the other hand, we analyse the function of these adverbs as boosters by considering the linguistic elements that co-occur with them and that affect this function, either to reinforce or to mitigate content.